2018
DOI: 10.1161/circresaha.118.313565
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum 299v Supplementation Improves Vascular Endothelial Function and Reduces Inflammatory Biomarkers in Men With Stable Coronary Artery Disease

Abstract: Rationale: A strong association has emerged between the gut microbiome and atherosclerotic disease. Our recent data suggest L. plantarum 299v (Lp299v) supplementation reduces infarct size in male rats. Limited human data are available on the impact of Lp299v on the vasculature. Objective: To determine whether oral Lp299v supplementation improves vascular endothelial function and reduces systemic inflammation in humans with stable coronary artery disease (CAD). Methods and Results: Twenty men with stable CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 66 publications
(60 reference statements)
8
110
0
2
Order By: Relevance
“…Many studies have revealed that Lactobacillus has the potential to regulate host immune systems, enhance gut metabolic capacities and maintain balance in the gut microbiota (Hou, Zeng, Yang, Liu, & Qiao, ; Zhang et al, ). Lactobacillus plantarum is considered an excellent probiotic in the gastrointestinal tracts of humans and animals and performs important probiotic actions, such as inhibiting Escherichia coli ‐induced intestinal permeability, reducing the incidence of Clostridium difficile , alleviating oxidative damage to the liver, improving growth performance and increasing intestinal immunity and anti‐inflammatory properties (de Vries, Vaughan, Kleerebezem, & de Vos, ; Dudzicz, Kujawa‐Szewieczek, Kwiecien, Wiecek, & Adamczak, ; Fak, Ahrne, Molin, Jeppsson, & Westrom, ; Herías et al, ; Khanian, Karimi‐Torshizi, & Allameh, ; Malik et al, ; Wullt, Johansson Hagslatt, Odenholt, & Berggren, ). Researches have shown that oral administration of L. plantarum can improve the immune responses and enhance the intestinal barrier function of weaning piglets (Wang, Ji, et al, ; Yang, Jiang, Zheng, Wang, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that Lactobacillus has the potential to regulate host immune systems, enhance gut metabolic capacities and maintain balance in the gut microbiota (Hou, Zeng, Yang, Liu, & Qiao, ; Zhang et al, ). Lactobacillus plantarum is considered an excellent probiotic in the gastrointestinal tracts of humans and animals and performs important probiotic actions, such as inhibiting Escherichia coli ‐induced intestinal permeability, reducing the incidence of Clostridium difficile , alleviating oxidative damage to the liver, improving growth performance and increasing intestinal immunity and anti‐inflammatory properties (de Vries, Vaughan, Kleerebezem, & de Vos, ; Dudzicz, Kujawa‐Szewieczek, Kwiecien, Wiecek, & Adamczak, ; Fak, Ahrne, Molin, Jeppsson, & Westrom, ; Herías et al, ; Khanian, Karimi‐Torshizi, & Allameh, ; Malik et al, ; Wullt, Johansson Hagslatt, Odenholt, & Berggren, ). Researches have shown that oral administration of L. plantarum can improve the immune responses and enhance the intestinal barrier function of weaning piglets (Wang, Ji, et al, ; Yang, Jiang, Zheng, Wang, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing of 16S ribosomal RNA (rRNA)-encoding gene of fecal samples was performed as described previously [15]. Feces from 3 aged rats (22-24 months old) with increased AF susceptibility residing and from young rats (2-3 months old) were collected and the samples were pooled by group.…”
Section: Methodsmentioning
confidence: 99%
“…2E). Lactobacillus is a probiotic which plays an important role in human health [25,26]. Thus, studying the interactions of this genus with other genera could provide insight into the functions of these species in the development of POF.…”
Section: Microbial Profilingmentioning
confidence: 99%